Exploring Online Peer Support Groups for Adults Experiencing Long COVID in the United Kingdom: Qualitative Interview Study - Hannah L S Day (JMIR Publications, 2022)
BackgroundLong COVID is an emerging public health concern. A growing number of individuals are experiencing prolonged, multifaceted health challenges and accompanying social impacts after COVID-19 infections. Support services in the United Kingdom remain insufficient and fraught with complexity. Responding to persistent gaps in care, patients joined forces in online peer support groups. However, little is known about how these groups impact patients with long COVID and their lived experiences of the condition. ObjectiveThe aim of this study is to explore the roles that online peer support groups take on and the impact they have on patients experiencing and recovering from long COVID in the United Kingdom. In doing so, this study aims to identify ways to inform future long COVID care, including online peer support and broader long COVID care structures. MethodsI conducted 11 semistructured interviews virtually on Zoom in July 2021. Participants had long COVID, were UK-based, and used long COVID online peer support groups. Topics discussed in interviews included what led participants to these groups, experiences within them, and feelings about the roles that the groups took on. I analyzed the results by manually conducting thematic analysis. ResultsLong COVID online peer support groups had numerous roles, significantly impacting users. I identified 5 themes and 13 subthemes through thematic analysis. The identified themes were as follows: (1) filling professional care gaps, (2) societal awareness, (3) engagement behavior, (4) diversity, and (5) social connections. Given the void of professional support, those experiencing long COVID gained some benefit from these groups. However, participants emphasized notable concerns about the all-encompassing roles these groups embody and speculated over potential improvements. ConclusionsIf used appropriately, online peer support groups could be immensely beneficial for patient well-being, beyond simply filling gaps in long COVID care. However, it appears many groups take on more than they can manage and become potentially harmful. Through prioritizing patient voices, long COVID care could be restructured to maximize peer support's benefits within broader care structures.